2012
DOI: 10.1017/s1355617712000896
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Awareness of Deficits in Alzheimer's Disease: The Role of Everyday Executive Dysfunction

Abstract: The present study analyzed the awareness of deficits in 117 mild Alzheimer's disease participants. Since few studies have examined the cognitive and behavioral domains of reduced awareness in detail, we performed a domain-specific assessment using the Awareness of deficit Questionnaire - Dementia scale with the novel aim of describing the relationship with everyday executive dysfunction. Through the use of the subtests of the Behavioral Assessment of the Dysexecutive Syndrome, we hypothesized that executive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
4
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 70 publications
(126 reference statements)
5
56
4
26
Order By: Relevance
“…Foram utilizados conceitos como falta de consciência do déficit (n = 7) 16,[19][20][21][22][23][24] , anosognosia (n = 4) 19,20,23,25 , insight (n = 2) 19,25 , falta de consciência das dificuldades cognitivas (n = 1) 10 e limitada consciência das deficiências (n = 1) 26 . A etiologia do comprometimento da consciência do dé-ficit foi relacionada a fatores biológicos como associações neuroanatômicas (n = 2) 16,23 , alterações neuropsiquiátricas (n = 3) 10,16,20 e a gravidade clínica da doença, também investigada pelo modelo psicossocial (n = 9) 10,16,19,[20][21][22][23][24][25] .…”
Section: Métodounclassified
See 2 more Smart Citations
“…Foram utilizados conceitos como falta de consciência do déficit (n = 7) 16,[19][20][21][22][23][24] , anosognosia (n = 4) 19,20,23,25 , insight (n = 2) 19,25 , falta de consciência das dificuldades cognitivas (n = 1) 10 e limitada consciência das deficiências (n = 1) 26 . A etiologia do comprometimento da consciência do dé-ficit foi relacionada a fatores biológicos como associações neuroanatômicas (n = 2) 16,23 , alterações neuropsiquiátricas (n = 3) 10,16,20 e a gravidade clínica da doença, também investigada pelo modelo psicossocial (n = 9) 10,16,19,[20][21][22][23][24][25] .…”
Section: Métodounclassified
“…A etiologia do comprometimento da consciência do dé-ficit foi relacionada a fatores biológicos como associações neuroanatômicas (n = 2) 16,23 , alterações neuropsiquiátricas (n = 3) 10,16,20 e a gravidade clínica da doença, também investigada pelo modelo psicossocial (n = 9) 10,16,19,[20][21][22][23][24][25] . Os artigos que relacionaram o comprometimento da consciência do déficit aos fatores psicossociais (n = 4) 21,22,24,26 abordaram aspectos como a influência de fatores psicológicos e sociais (n = 1) 21 , o impacto nas AVD (n = 2) 22,26 e o valor prognóstico da avaliação global do cuidado na avaliação médica (n = 1) 24 .…”
Section: Métodounclassified
See 1 more Smart Citation
“…Studies have also shown that both executive functioning performance and global awareness decline over time (Amanzio et al, 2013;Mathalon et al, 2003;Ott et al, 1996;Suchy et al, 2011;Van Wielingen et al, 2004). However, there…”
Section: Discussionmentioning
confidence: 99%
“…Although research into executive functioning awareness is limited, studies have operationalized this awareness into several forms, from success at daily activities (Ott et al, 1996;Suchy, Kraybill, & Franchow, 2011) to finance management (Van Wielingen, Tuokko, Cramer, Mateer, & Hultsch, 2004) to error monitoring (Amanzio et al, 2013;Mathalon et al, 2003). A common theme among such studies is that both executive functioning performance and awareness deteriorate between healthy aging and early stages of dementia.…”
Section: Executive Functioning Awareness Memory In Context and Longmentioning
confidence: 99%